Comparative genome analysis of Streptococcus suis serotype 5 strains from humans and pigs revealed pathogenic potential of virulent, antimicrobial resistance, and genetic relationship - Kerdsin, Anusak; Hatrongjit, Rujirat; Wongsurawat, Thidathip; Jenjaroenpun, Piroon; Zheng, Han; Chopjitt, Peechanika; Boueroy, Parichart; Fittipaldi, Nahuel; Segura, Mariela; Gottschalk, Marcelo (Microbes and infection, 2025)
Streptococcus suis is a causative agent of swine and human infections. Genomic analysis indicated that eight S. suis serotype 5 strains recovered from human patients and pigs carried many virulence-associated genes and markers defining pathogenic pathotypes. The strains were sequence types diverse and clustered within either minimum core genome group 3 (MCG-3) or MCG-7-3. Almost all the serotype 5 strains were non-susceptible to penicillin, ceftriaxone, erythromycin, and levofloxacin. Resistance to tetracycline and clindamycin was observed in all strains. The antimicrobial resistance genes tet(O), tet(O/W/32/O), tet(W), tet(44), erm(B), ant(6)-Ia, lsaE, and lnuB were found in these strains. Moderate-to-large numbers of substitutions were observed in three penicillin-binding proteins (PBP)—PBP1A, PBP2B, and PBP2X—in the penicillin-non-susceptible serotype 5 isolates that were involved in β-lactam-non-susceptibility. Comparative genomics between the serotype 5 and 2 strains revealed that only 15 genes absent from the serotype 2 strains were shared by all the serotype 5 strains. However, some additional genes were present only in some of the serotype 5 strains. This study highlighted the pathogenic potential of virulent serotype 5 strains in humans and pigs and the need for increased monitoring of penicillin-non-susceptibility in S. suis serotypes other than for serotype 2.